2018
DOI: 10.1186/s40814-018-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, crossover pilot study of losartan for pediatric nonalcoholic fatty liver disease

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is the most common liver disease in children, and currently, there are no FDA-approved therapies. Plasminogen activator inhibitor-1 (PAI-1) is elevated in children with NAFLD and associated with increased disease severity. Losartan potassium (losartan) is an angiotensin II receptor blocker (ARB) that reduces PAI-1 production and improves insulin sensitivity that has been proposed as a treatment for pediatric NAFLD but has not previously been tested.MethodsThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…This molecule has been proposed as a novel treatment of MAFLD by improving steatosis and fibrosis. Preliminary evidence (phase II) suggests that losartan treatment is safe over 8 weeks in children with MAFLD and supports consideration of larger studies to test its efficacy [ 73 ]. A clinical trial evaluating the antagonist of SGLT-2 has been initiated in children, but data are still lacking due to the difficulties of recruiting patients during the COVID-19 pandemic (NCT03867487).…”
Section: Potential Recommendationsmentioning
confidence: 99%
“…This molecule has been proposed as a novel treatment of MAFLD by improving steatosis and fibrosis. Preliminary evidence (phase II) suggests that losartan treatment is safe over 8 weeks in children with MAFLD and supports consideration of larger studies to test its efficacy [ 73 ]. A clinical trial evaluating the antagonist of SGLT-2 has been initiated in children, but data are still lacking due to the difficulties of recruiting patients during the COVID-19 pandemic (NCT03867487).…”
Section: Potential Recommendationsmentioning
confidence: 99%
“…Losartan is currently being compared to placebo in 8 to 17 year olds with histological evidence of NAFLD. Losartan is thought to reduce plasminogen activator inhibitor-1 (PAI-1), which is elevated in children with NAFLD and associated with increased disease severity [72].…”
Section: Current Clinical Trialsmentioning
confidence: 99%
“…Although there is paucity of data on the effect of RAAS inhibitors on NAFLD in humans, a recent study suggested that RAAS inhibitors can decrease the risk for NAFLD development and progression in obese patients ( 106 ). In a randomized, double-blind, placebo-controlled, phase 2a trial that included 12 children with NASH, losartan improved ALT and AST levels ( 107 ). In this context, the RELIEF-NAFLD (Role of Lisinopril in Preventing the Progression of Non-Alcoholic Fatty Liver Disease; NCT04550481 ) trial is an ongoing study to examine the effect of lisinopril on the prevention and progression of NAFLD.…”
Section: Management Of Nafld-related Hfpef Phenotypesmentioning
confidence: 99%